Adoptive transfer of Tc1 or Tc17 cells elicits anti-tumor immunity against established melanoma through distinct mechanisms() - Yu, Yu (2013)
Adoptive cell transfer (ACT) of ex vivo activated autologous tumor-reactive T cells is currently one of the most promising approaches for cancer immunotherapy. Recent studies provided some evidence that Th17/Tc17 cells may exhibit potent anti-tumor activity, but the specific mechanisms have not been completely defined. In the present study, we used a murine melanoma lung-metastasis model and tested the therapeutic effects of gp100-specific polarized Tc1 or Tc17 cells combined with autologous BMT after total TBI. BMT combined with ACT of anti-tumor (gp100-specific) Tc17 cells significantly suppressed the growth of established melanoma, whereas Tc1 cells induced long-term tumor regression. After ACT, Tc1 cells maintained their phenotype to produce IFNγ but not IL-17. However, although Tc17 cells largely preserved their ability to produce IL-17, a subset secreted IFNγ or both IFNγ and IL-17, indicating the plasticity of Tc17 cells in vivo. Furthermore, after ACT the Tc17 cells had a long-lived effector T cell phenotype (CD127hi/KLRG-1low) as compared to Tc1 cells. Mechanistically, Tc1 cells mediated anti-tumor immunity primarily through the direct effect of IFNγ on tumor cells. In contrast, despite the fact that some Tc17 cells also secreted IFNγ, Tc17-mediated anti-tumor immunity was independent of the direct effects of IFNγ on the tumor. Nevertheless, IFNγ played a critical role by creating a microenvironment that promoted Tc17-mediated anti-tumor activity. Taken together, these studies demonstrate that both Tc1 and Tc17 cells can mediate effective anti-tumor immunity through distinct effector mechanisms, but Tc1 cells are superior to Tc17 cells in mediating tumor regression.